Joining and Characterization of SS-430 Using Microwave Processing Method - Singh, Navjot (My University, 2016)
Heating of the materials by using the radiations of the microwave is not a new application; some newer applications are emerging in the field of processing of materials by using the microwave radiations due to which it becomes a novel processing technique. Many authors have worked on ceramic materials and their sintering by using the microwave radiations. Now a days the applications of the microwave is being extended up to the sintering of the metallic powders. In the past years; many researches has processed the metallic powders and their sintering by using the microwave radiations; and used them in different applications like cladding as well as joining of the materials. The present work is based upon the joining of SS-430 materials through microwave radiations. XRD, EDS and SEM were used to characterize the prepared samples. Mechanical characterization like tensile testing was performed to saw the strength of the joint and Vicker’s micro hardness tester was used to check the hardness of the joint. Observed results showed that the SS-430 material was successfully joined by the microwave radiations by using nickel as a base powder (EWAC). A cellular structure having less defects was observed by using the metallurgical characterizations. The mechanical characterizations of joints shows that due to better metallurgical bonding and diffusion, mechanical strength was increased and also the defects were less. The ultimate tensile strength which was observed during the experiment was 471 MPa. Hardness was higher of the joint due to the presence of carbon which was absorbed from graphite sheet resulted in the formation of carbides in the microstructures of microwave processed joints.
Keywords: microwave,carbides, strength